Examining aging sexual stigma attitudes among adults by gender, age, and generational status - Syme, Maggie; Cohn, Tracy J. (My University, 2016)
Objectives: Stigma related to later life sexuality could produce detrimental effects for older adults, through individual concerns and limited sexual health care for older adults. Identifying groups at risk for aging sexual stigma will help to focus interventions to reduce it. Accordingly, the purpose of this study was to examine cross-sectional trends in aging sexual stigma attitudes by age group, generational status, and gender. Method: An online survey was administered to a national sample of adults via a crowdsourcing tool, in order to examine aging sexual stigma across age groups, generational status, and gender (N = 962; 47.0% male, 52.5% female, and .5% other; mean age = 45 years). An aging sexual stigma index was formulated from the attitudinal items of the Aging Sexual Knowledge and Attitudes Scale. Results: This sample reported moderately permissive attitudes toward aging sexuality, indicating a low level of aging sexual stigma. Though descriptive data showed trends of stigma attitudes increasing with age and later generations, there were no significant differences between age groups or generations in terms of aging sexual stigma beliefs. Men, regardless of age and/or generation, were found to espouse significantly higher stigmatic beliefs than women or those reporting ‘other’ gender. Conclusions: Aging sexual stigma beliefs may not be prevalent among the general population as cohorts become more sexually liberal over time, though men appear more susceptible to these beliefs. However, in order to more comprehensively assess aging sexual stigma, future research may benefit from measuring explicit and implicit aging sexual stigma beliefs.
Keywords: Aging; Sexuality; Stigma; Attitudes